The mountain is coming to you - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
We all need mountains, and should stand back and treat them with the utmost respect. Welcome to 2002, the Year of the Mountain.Most people have a complex relationship with mountains. Even if you have never seen one in the flesh, as it were, they...